Role of Vitamin B12 in Mental Health of Children and Adolescents: A Systematic Review - Rizwan Taj; Shaista Faheem; Asima Mehboob Khan; Arham Yahya Khan; Aamir Naveed (University of Lahore, 2024)
Objective: To investigate the role of Vitamin B12 in mental health outcomes among children and adolescents. Methodology: From January-April, 2023, following PRISMA guidelines, a comprehensive search strategy was employed across databases, including PubMed, PsycINFO, Cochrane Library, and Google Scholar to identify relevant studies linking Vitamin B12 levels with mental health outcomes in children and adolescents. The initial search yielded 150 records, leading to the inclusion of 10 quantitative studies, including one cross-sectional, seven case-controls, and two systematic reviews. Parameters recorded included study design, population sample size, age of the participants, place of study, biochemical investigations conducted and mental health disorders as outcomes. The biochemical markers examined across all 10 studies included vitamin B12, folate, homocysteine, ferritin, fattyacids ,inorganic phosphorus, and 25-OH vitamin D. These markers were assessed to understand their associations with various mental health disorders such as depression, anxiety, attention deficit hyperactivity disorder, and autism spectrum disorders. Results: Out of the 10 studies included, 6 studies reported significant improvements in symptoms of depression and anxiety with vitamin B12 supplementation. However, 4 studies found no significant association between B12 supplementation and the studied disorders. Three studies out of 6 observed lower levels of vitamin B12 in patients with ADHD and ASD compared to healthy controls, suggesting a potential role for B12 supplementation in these conditions.From the biomarkers identified, lower levels of vitamin B12 were associated with depression among children, while increased intake of certain nutrients such as fiber, omega-3 fatty acids, and vitamin B12 were marginally associated with reduced odds of aggressive be- havior. Furthermore, there was a significant decrease in symptoms of depression and anxiety following supplementation with B vitamins and/or vitamin D. Conclusion: Supplementation of B12, could help improve mental health issues like depression, anxiety, aggression, and ADHD.